La gloria, esa plaga de nuestra pobre América del Sud - Alejandro M. Rabinovich (Nuevo mundo - Mundos Nuevos, 2009)
This article explores Rio de la Plata's war culture during the early independent period. In order to recover the specificity of the warrior ethos, it focuses on the notion of military glory, showing how it actually determined behavioral patterns and institutional designs. Our regular understanding of combat experiences, personal strategies, popular sociability and institutional forms is here redeployed in order to acknowledge a situation of protracted warfare and extreme social militarization.